Edukasi Pengetahuan Tentang Kebencanaan untuk Kesiapsiagaan Banjir di SMP Negeri 16 Medan: Penelitian - Meutia Nanda; Alya Najwa; Jihan Nabila Ritonga; Aulia Zahra Ritonga; Rifa Dwi Ramadhani; Alfira Budiman (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Flooding is one of the most frequent hydrometeorological disasters and has a significant impact on social, economic, and health aspects of society, requiring efforts to improve preparedness through education on flood disasters in schools, especially in flood-prone areas. The purpose of this study was to determine the effect of education on students' knowledge and preparedness in facing flood disasters. The method used in this study was quantitative with a pre-post test one group design and involved 50 ninth-grade students. The measurement instrument was a questionnaire sheet given before and after education. Data analysis used a paired t-test. The results showed an increase in the average knowledge score from 5.60 (pre-test) to 7.00 (post-test) with a significance value of p < 0.001, which means that education has a significant effect on increasing students' knowledge. A significant improvement was seen in the material on the causes of flooding, mitigation and capabilities, as well as preparedness and information utilization, with the post-test showing a correct answer percentage of over 90%. Education on flood disasters has proven effective in improving students' understanding of the causes, mitigation, and flood response measures.